2013
DOI: 10.1128/jb.00663-13
|View full text |Cite
|
Sign up to set email alerts
|

Role for cis -Acting RNA Sequences in the Temperature-Dependent Expression of the Multiadhesive Lig Proteins in Leptospira interrogans

Abstract: fThe spirochete Leptospira interrogans causes a systemic infection that provokes a febrile illness. The putative lipoproteins LigA and LigB promote adhesion of Leptospira to host proteins, interfere with coagulation, and capture complement regulators. In this study, we demonstrate that the expression level of the LigA and LigB proteins was substantially higher when L. interrogans proliferated at 37°C instead of the standard culture temperature of 30°C. The RNA comprising the 175-nucleotide 5= untranslated regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 72 publications
(85 reference statements)
2
47
0
2
Order By: Relevance
“…Previous research showed that LigA and LigB are surface-exposed proteins (22) and that they play a role in the adhesion of spirochetes to extracellular matrix proteins, complement regulators, and animal cells (15,23,24). Furthermore, single-gene mutants of either ligA in L. interrogans serovar Manilae strain L495 or ligB in L. interrogans serovar Copenhageni strain Fiocruz L1-130 did not reduce virulence in standard animal models and remained recoverable from animal tissue (25,26).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research showed that LigA and LigB are surface-exposed proteins (22) and that they play a role in the adhesion of spirochetes to extracellular matrix proteins, complement regulators, and animal cells (15,23,24). Furthermore, single-gene mutants of either ligA in L. interrogans serovar Manilae strain L495 or ligB in L. interrogans serovar Copenhageni strain Fiocruz L1-130 did not reduce virulence in standard animal models and remained recoverable from animal tissue (25,26).…”
Section: Resultsmentioning
confidence: 99%
“…A TALE gene specific for the leptospiral immunoglobulinlike (lig) genes ligA and ligB was designed to anneal to the sequence 5=-TCCAATAAATCTTAAGAGA-3=. This sequence corresponds to the Ϫ10 promoter region, which is a homologous region 170 bp upstream of the ϩ1 sites of ligA (lmanv2_30028) and ligB (lmanv2_350013) (15). Three biologically distinct TALE lig transformants were characterized: TALE lig1 , TALE lig2 , and TALE lig3 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…LigA is an outer membrane protein exposed on and released from the leptospiral surface (22,23). Several lines of evidence suggest that ligA is upregulated during infection of the mammalian host, including induction of expression by physiologic osmolarity (23) and temperature (24) and an early humoral immune response to the Lig proteins during infection (25). Several groups have reported that immunization with the LigA unique region, consisting of domains 7 to 13 (LigA7-13), confers protection from intraperitoneal (i.p.)…”
mentioning
confidence: 99%
“…indicam uma origem comum e revelaram uma grande divergência nos membros de Bartonella (LEHMANN et al, 2013) A família DUF_61 também está presente em bactérias patogênicas responsáveis por doenças gástricas e enterohepáticas em animais e/ou humanos, como espécies não pilóricas do gênero Helicobacter, espécies de Campylobacter e a espécie Piscirickettsia salmonis (O"ROURKE et al, 2001;FRYER & HEDRICK, 2003;KERSULYTE et al, 2013;MÉNARD et al, 2014;KAAKOUSH et al, 2015).…”
Section: Discussionunclassified